Factors influencing malaria knowledge, attitude and practice in Gwagwalada - Oguntade, Emmanuel Segun; Shohaimi, Shamarina; Nallappan, Meenakshii; Lamidi-Sarumoh, Alaba Ajibola (Galore Knowledge Publication, 2018)
Malaria epidemics are widespread in the tropics. Studies showed that malaria mitigation depends on case management, vector control and use of preventive measures. However, knowledge, attitude and practice (KAP) regarding malaria are paramount in the mitigation campaign which has not been given relevance in Sub-Sahara Africa. This study explores factors influencing KAP regarding malaria in Gwagwalada. A cross-sectional survey was done in four different sites in Gwagwalada between March and September 2016. A structured validated questionnaire was used to obtain information from 384 respondents. There was a statistical comparison of the KAP among the different sites. Majority of participants had heard about malaria (99.3%) but only 20% had good knowledge and 14.4% have good practice scores. There was no significant difference in the KAP scores of the four different sites examined. Of the selected socio-demographic predictors, occupation and education of participants were significantly different for attitude scores, while age and occupation were associated with knowledge scores. Only marital status was significant with good practice. The study found increased odds of good knowledge if the participants worked with the government (OR:1.34; .95CI:0.50,3.48) and decreased in odds of having good knowledge if the participants were older than 47 years (OR:0.98; 0.95CI:0.34,3.17). At multivariate level, only respondent’s education significantly predicts attitude level (P <0.05) while age and occupation were independent predictors of level of knowledge. Age and education are key determinant factors of malaria KAP in the study area. Therefore, health education should target people with lower education and older age at community level.